A Comparative Study of the Theme of "the Justification of God’s Providence" in the Outlooks of Sa’di and Alexander Pope - Shadi Mohyeddin Ghomshei; Jalal Sokhanvar (ادبیات تطبیقی, 2020)
1.      Introduction